Pengaruh Senam Aerobik Low Impact dalam Menurunkan Tekanan Darah Penderita Hipertensi - Syavinka, Zuan Nun Alea; Yuniartika, Wachidah (Faletehan Health Journal, 2024)
Hypertension is a growing global health problem that can lead to serious complications such as heart disease, stroke, and kidney failure. This condition is often overlooked, necessitating accessible non-pharmacological intervention strategies such as low-impact aerobic exercise. This study aims to explore the effects of low-impact aerobic exercise in lowering blood pressure of hypertensive patients. This study employed a quantitative approach with a pre-experimental design. The study population consisted of 35 hypertensive patients at the working area of Baki Public Health Center with inclusion criteria, namely: patients with mild to moderate hypertension who were capable to do physical activity and not routinely taking medication. The exercise intervention was conducted for 8 weeks with a frequency of 2-3 times per week and a duration of 15 minutes per session. The gathered data was analyzed by using Wilcoxon signed-rank test, obtaining a P-value of < 0.001 for systolic blood pressure and 0.001 for diastolic blood pressure. The result of the data analysis identified that low impact aerobic exercise has a significant effect in lowering hypertension.